Les Forces du bien et du mal dans les premiers siècles de l’Église: Acts du colloque de Tours, septembre 2008. Edited by Yves-Marie Blanchard, Bernard Pouderon, and Madeleine Scopello - Meredith, Antony (The journal of theological studies, 2013)
These 22 papers, all in French, were delivered at the fourth patristic conference held in the University of Tours, 11–13 September 2008. The first five deal with the philosophical problem of good and evil, the next six with temptation and choice, and the final eleven with figures and types., Although all the contributions are very exact and wide-ranging, there is no general thesis offered, apart from the basic title. Some of the authors addressed, like Tertullian and Cyprian, are well enough known; others, like Corippus, a sixth-century grammaticus from North Africa, who identifies evil with barbarian paganism, are, at least to the present reviewer, somewhat obscure. There are several omissions.